2014
DOI: 10.1088/1475-7516/2014/10/061
|View full text |Cite
|
Sign up to set email alerts
|

Power spectrum tomography of dark matter annihilation with local galaxy distribution

Abstract: Abstract. Cross-correlating the gamma-ray background with local galaxy catalogs potentially gives stringent constraints on dark matter annihilation. We provide updated theoretical estimates of sensitivities to the annihilation cross section from gamma-ray data with Fermi telescope and 2MASS galaxy catalogs, by elaborating the galaxy power spectrum and astrophysical backgrounds, and adopting the Markov-Chain Monte Carlo simulations. In particular, we show that taking tomographic approach by dividing the galaxy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 61 publications
(178 reference statements)
0
48
0
Order By: Relevance
“…In addition, we find that for 10 13 GeV m dm 10 16 GeV the PAO constraints are comparable to those obtained with Fermi-LAT. Although the constraints obtained with our extragalactic predictions are found to be weaker than those using the Galactic component, our simulations could potentially be used in future analyses of all sky gamma-ray analyses of, for example, tomographic cross-correlation using the local galaxy distributions [83][84][85][86][87][88].…”
Section: Constraints On Dark Matter Lifetimementioning
confidence: 99%
“…In addition, we find that for 10 13 GeV m dm 10 16 GeV the PAO constraints are comparable to those obtained with Fermi-LAT. Although the constraints obtained with our extragalactic predictions are found to be weaker than those using the Galactic component, our simulations could potentially be used in future analyses of all sky gamma-ray analyses of, for example, tomographic cross-correlation using the local galaxy distributions [83][84][85][86][87][88].…”
Section: Constraints On Dark Matter Lifetimementioning
confidence: 99%
“…[52], which analyzed the IGRB data and found that they were spatially correlated with galaxy distributions. Compared to the commonly adopted spectral analysis, the tomographic method allows us to efficiently extract a dominant IGRB component in certain redshift ranges following galaxy catalogs, as originally proposed for dark matter detection [53][54][55]. This provides stringent constraints on astrophysical sources [52] and dark matter [56].…”
Section: Tomographic Constraints On High-energy Neutrinos Of Hadronucmentioning
confidence: 99%
“…It is suggested that the crosscorrelation of local galaxies and the cosmic infrared back-ground helps to infer the star-forming activity in galaxies over a wider range of redshifts [17,56,57], while observations of galaxy clusters, radio galaxies, and the CMB lensing effect will tighten the constraints on the contribution from misaligned AGN [18,20]. Furthermore, a tomographic approach using γ-ray energies and redshifts of LSS tracers will be viable with upcoming galaxy surveys [25,58]. Ultimately, by putting all these information together, we will be able to understand the contributions to the EGB and perform stringent searches on the particle nature of dark matter.…”
Section: Conclusion and Discussionmentioning
confidence: 99%